Interest rate volatility: a consol rate-based measure - Vincent Brousseau; Alain Durré (European Central Bank (ECB), 2013)
In this paper we propose a new methodology to estimate the volatility of interest rates in the euro area money market. In particular, our approach aims at avoiding the limitations of currently available measures, i.e. the dependency on arbitrary choices in terms of maturity and frequencies and/or of factors other than pure interest rates, e.g. credit risk or liquidity risk. The measure is constructed as the implied instantaneous volatility of a consol bond that would be priced on the EONIA swap curve over the sample period from 4 January 1999 to 20 November 2012. We show that this measure tracks well the historical volatility, in the sense that dividing the consol excess returns by this volatility removes nearly entirely excess of kurtosis and volatility clustering, bringing them close to an ordinary Gaussian white noise.
Keywords: E43; E58; C22; C32; 330; Consol rate; historical volatility; interbank offered interest rates; Overnight money market